Lessons Learned From Trials Targeting Cytokine Pathways in Patients With Inflammatory Bowel Diseases - Abraham, Clara (Gastroenterology, 2016)
Insights into the pathogenesis of inflammatory bowel diseases (IBD) have provided important information for the development of therapeutics. Levels of interleukin 23 (IL23) and T-helper (Th) 17 cell pathway molecules are elevated in inflamed intestinal tissues of patients with IBD. Loss of function variants of the interleukin 23 receptor gene (IL23R) protect against IBD, and in animals, blocking IL23 reduces severity of colitis. These findings indicated that the IL23 and Th17 cell pathways might be promising targets for treatment of IBD. Clinical trials have investigated the effects of agents designed to target distinct levels of the IL23 and Th17 cell pathways, and the results are providing insights into IBD pathogenesis and additional strategies for modulating these pathways. Strategies to reduce levels of proinflammatory cytokines more broadly and increase anti-inflammatory mechanisms are also emerging for treatment of IBD. The results from trials targeting these immune system pathways have provided important lessons for future trials. Findings indicate the importance of improving approaches to integrate patient features and biomarkers of response with selection of therapeutics.